Strategi Penganggaran Yang Efektif Untuk Mencapai Keberlanjutan Finansial Perusahaan - Muammar Muammar; Andira Andira; Mentari Mentari; Natasya Natasya; Eprilia Eprilia (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Every business wants to achieve financial sustainability. To achieve this goal, the use of effective budgeting strategies is essential. This article will discuss several budgeting strategies that can help businesses achieve this financial sustainability.The ability of a company to operate consistently and profitably over the long term is called financial sustainability. This means that the company is able to generate sufficient income to pay debts, cover operational costs, and make investments to encourage future growth. To achieve financial sustainability, companies must use effective budgeting strategies, which include thorough financial planning, strict cost control, wise investments, and sustainability principles. By implementing this strategy, companies can increase profitability, progress and sustainability in the long term.